ESCMID generic competencies in antimicrobial prescribing and stewardship: towards a European consensus. (January 2019) - Dyar, O.J.; Beović, B.; Pulcini, C.; Tacconelli, E.; Hulscher, M.; Cookson, B.; ,
Abstract: Objective: To develop a consensus-based set of generic competencies in antimicrobial prescribing and stewardship for European prescribers through a structured consensus procedure. Methods: The RAND-modified Delphi procedure comprised two online questionnaire rounds, a face-to-face meeting between rounds, and a final review. Our departure point was a set of competencies agreed previously by consensus among a UK multi-disciplinary panel, and which had been subsequently revised through consultation with ESCMID Study Group representatives. The 46 draft competency points were reviewed by an expert panel consisting of specialists in infectious diseases and clinical microbiology, and pharmacists. Each proposed competency was assessed using a nine-point Likert scale, for relevance as a minimum standard for all independent prescribers in all European countries. Results: A total of 65 expert panel members participated, from 24 European countries (one to six experts per country). There was very high satisfaction (98%) with the final competencies set, which included 35 competency points, in three sections: core concepts in microbiology, pathogenesis and diagnosing infections (11 points); antimicrobial prescribing (20 points); and antimicrobial stewardship (4 points). Conclusions: The consensus achieved enabled the production of generic antimicrobial prescribing and stewardship competencies for all European independent prescribers, and of possible global utility. These can be used for training and can be further adapted to the needs of specific professional groups.